Securing 5G-enabled IoT with Blockchain: A Technical Review - Goswami, Bidisha; Choudhury, Hiten (SN computer science, 2025)
The 5G network, with its high bandwidth, low latency, and broad connectivity, is becoming the preferred communication technology for IoT devices. With the growth of IoT applications like smart homes, healthcare, and metering, the number of IoT devices is set to increase rapidly, raising concerns about data security, privacy and authentication throughput. Blockchain has emerged as a promising solution to address these concerns due to its decentralized architecture. This survey reviews blockchain-based solutions for securing 5G-enabled IoT devices, focusing on device authentication and providing a comparative analysis of security, performance, and implementation platforms. It also highlights promising avenues for future investigation in this area.